How to be an ally : actions you can take for a stronger, happier workplace - Epler, Melinda Briana (McGraw Hill, 2021)
"An original and insightful roadmap on how to become a more inclusive and empathetic leader All of us can be better allies for each other, creating stronger and happier workplaces together. Allyship is about understanding the imbalance in opportunity and working to correct it. How to Be an Ally reveals that the key to true inclusion, equity, and diversity is allyship. Drawing from her experience as a strategic advisor for tech companies, startups, tech hubs, and governments around the world, Melinda Briana Epler provides valuable insights on how business leaders can create a more equitable workplace by leading the change. You'll learn how to implement big and small changes to build a diverse team and ensure everyone on your team is included, heard, understood, and acknowledged. Building on that inclusion, you'll be able to grow a stronger, more successful organization. Original and insightful, How to Be an Ally humanizes diversity and inclusion, and facilitates greater empathy and understanding between people of all backgrounds, teaching us that each of us can learn to understand the imbalance in opportunity, work to correct it, and help create a better workplace for ourselves and our colleagues"--